The Effectiveness of Transcranial Magnetic Stimulation in Post Stroke Dysphagia: A Case Report - Suska Lara Ginting; Yetty Hambarsari; Rivan Danuaji; Baarid Luqman Hamidi (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2024)
Background: A 72-year-old male, experiencing dysphagia and left-sided weakness for six months post-stroke, encountered challenges such as coughing and choking during the consumption of liquids and soft foods, along with a prolonged meal-swallowing process. Magnetic Resonance Imaging (MRI) revealed bilateral thrombotic infarction and left lateralization. Case: The Gugging Swallowing Screening Scale (GUSS) assessment demonstrated severe impairment with a total score of 7, persisting despite conventional physiotherapy attempts to improve swallowing function. Subsequently, repetitive transcranial magnetic stimulation (rTMS) was implemented, involving high-intensity stimulation in the ipsilesional hemisphere and low-intensity stimulation in the contralesional hemisphere. Remarkably, one-month post-rTMS, the patient displayed significant progress, evidenced by an improved GUSS score of 15, indicating enhanced swallowing function. Discussion: This case emphasizes the positive impact of bilateral rTMS hemispheric stimulation on post-stroke dysphagia. The strategic application of high-intensity ipsilesional and low-intensity contralesional stimulation emerged as an effective intervention for alleviating swallowing difficulties. Conclusion: These findings highlight the potential of rTMS as an innovative therapeutic approach for persistent dysphagia following a stroke. Repetitive transcranial magnetic stimulation (rTMS) has shown significant potential as an innovative and effective therapeutic approach for managing persistent post-stroke dysphagia. This case highlights the role of tailored rTMS protocols in improving swallowing function, with recovery influenced by factors such as stroke severity, dysphagia severity, age, nutritional status, timing of intervention, and lesion location.